Bioethics, culture and infanticide in Brazilian indigenous communities: the Zuruahá case Bioética, cultura e infanticídio em comunidades indígenas brasileiras: o caso Zuruahá - Saulo Ferreira Feitosa; Volnei Garrafa; Gabriele Cornelli; Carla Tardivo; Samuel José de Carvalho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
This article analyzes the practice of infanticide in indigenous communities in Brazil. Taking as a reference point a specific case involving two children of the Zuruahá people, it takes a broader look at the issue and discusses how infanticide is understood among other indigenous peoples. A debate focusing specifically on this topic that took place during a public hearing held in the Brazilian National Congress in December 2005 has also been taken into consideration in this discussion. In view of the positions adopted as a result of the hearing, this paper seeks to identify the ethical problems and moral dilemmas relating to the subject, by putting them into context and analyzing them in the light of respect for cultural pluralism. Seeking to contribute to the debate, the authors analyze the possibilities for intervention in the traditional practices of infanticide, while rejecting those positions that are not anchored in an attitude of profound respect for other people's cultures or that do not create conditions for dialogue between individuals or groups with different moralities. O artigo analisa a prática do infanticídio em comunidades indígenas brasileiras. Tomando como referência um caso específico envolvendo duas crianças do povo Zuruahá, focaliza o tema sob uma abordagem mais abrangente e discute como o infanticídio é interpretado em outros povos indígenas. Foram considerados, na discussão, os debates ocorridos durante a Audiência Pública realizada no Congresso Nacional Brasileiro, em dezembro de 2005, que analisou o tema, além de revisão bibliográfica. Diante dos posicionamentos assumidos naquela audiência, procurou-se identificar os problemas éticos e os dilemas morais, contextualizando-os e analisando-os à luz do respeito ao pluralismo cultural. A fim de contribuir com o debate, os autores analisam as possibilidades de intervenção nas práticas tradicionais de infanticídio, recusando qualquer opção que não esteja ancorada numa atitude de profundo respeito pela cultura de outros povos ou que não apresente condição de dialogar com indivíduos ou grupos com diferentes moralidades.